Rhodococcus sp. Q5, a novel agarolytic bacterium isolated from printing and dyeing wastewater - Feng, Zehua; Peng, Lin; Chen, Mei; Li, Mengying (Folia microbiologica, 2012)
An agar-degrading bacterium, Rhodococcus sp. Q5, was isolated from printing and dyeing wastewater using a mineral salts agar plate containing agar as the sole carbon source. The bacterium grew from pH 4.0 to 9.0, from 15 to 35°C, and in NaCl concentrations of 0-5 %; optimal values were pH 6.0, 30°C, and 1 % NaCl. Maximal agarase production was observed at pH 6.0 and 30°C. The bacterium did not require NaCl for growth or agarase production. The agarase secreted by Q5 was inducible by agar and was repressed by all simple sugars tested except lactose. Strain Q5 could hydrolyze starch but not cellulose or carboxymethyl cellulose. Agarase activity could also be detected in the medium when lactose or starch was the sole source of carbon and energy. Strain Q5 could grow in nitrogen-free mineral media; an organic nitrogen source was more effective than inorganic carbon sources for growth and agarase production. Addition of more organic nitrogen (peptone) to the medium corresponded with reduced agarase activity.
Keywords: chlorid sodný; bakteriální proteiny; Sodium Chloride; Bacterial Proteins; Industrial Waste; Rhodococcus; Phylogeny; Molecular Sequence Data; glykosidhydrolasy; molekulární sekvence - údaje; fylogeneze; Wastewater; Agar; Glycoside Hydrolases; průmyslový odpad; agar; odpadní voda